(untitled) (Progress Annals: Journal of Progressive Research, 2024)
This article examines the coordination issues between state financial control bodies and internal audit services, focusing on the improvement of financial transparency and the prevention of financial irregularities. Using recent developments in Uzbekistan as a case study, the article highlights the importance of information exchange, standardization of methodologies, and the alignment of internal audit practices with international standards. The article also explores challenges in the regulatory framework and provides recommendations for enhancing cooperation between these entities